1998
DOI: 10.1002/(sici)1096-9861(19980126)390:4<455::aid-cne1>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical demonstration of locustatachykinin‐related peptides in the central complex of the locust brain

Abstract: The central complex, a highly ordered neuropil area in the insect brain, plays a role in motor control and spatial orientation. To further elucidate the neurochemical architecture of this brain area, we have investigated the distribution and morphology of neurons containing locustatachykinin I/II-related substances in the central complex of the locust Schistocerca gregaria. The central complex is innervated by at least 66 locustatachykinin I/II-immunoreactive neurons, which belong to two sets of tangential neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 46 publications
11
77
0
Order By: Relevance
“…The anti-locustatachykinin II (Lom-TK II) antiserum (K1-50820091) was donated by Dr. Hans Agricola (University of Jena, Jena, Germany) and was used at a dilution of 1:30,000. Its specificity on S. gregaria brain sections has been characterized by Vitzthum and Homberg (1998). For staining of neurons containing A-type allatostatins (AST-A), an antiserum against Diploptera punctata allatostatin 7 was used.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-locustatachykinin II (Lom-TK II) antiserum (K1-50820091) was donated by Dr. Hans Agricola (University of Jena, Jena, Germany) and was used at a dilution of 1:30,000. Its specificity on S. gregaria brain sections has been characterized by Vitzthum and Homberg (1998). For staining of neurons containing A-type allatostatins (AST-A), an antiserum against Diploptera punctata allatostatin 7 was used.…”
Section: Methodsmentioning
confidence: 99%
“…4a) has a morphology similar to the locustatachykinin-immunoreactive columnar neurons of the central body, type IV, stained with antisera against Locusta migratoria tachykinin II (Vitzthum and Homberg 1998). Arborizations were found in layers I and IIa of the CBU and in the anterior dorsal shell of the LAL, but primary neurites and cell bodies could not be identified.…”
Section: Citrulline Immunostainingmentioning
confidence: 99%
“…TK immunostaining of the central complex in various other insect species also shows obvious diversity in neuron types. For instance, in the locust four different populations of columnar fb neurons and two different populations of tangential neurons have been identified (Vitzthum and Homberg, 1998). Based on morphology it has been suggested that the main inputs to the central complex are through large field tangential neurons and that main output channels are through columnar elements, while pontine neurons are believed to be intrinsic elements connecting columns and layers within the central complex (Hanesch et al, 1989;Heinze and Homberg, 2008).…”
Section: Dtks: Distribution and Contribution To Locomotor Behaviormentioning
confidence: 99%